2021
DOI: 10.1093/rap/rkab029
|View full text |Cite
|
Sign up to set email alerts
|

Impaired hand function and performance in activities of daily living in systemic lupus erythematosus, even in patients achieving lupus low disease activity state (LLDAS)

Abstract: Objective To examine hand function and performance in activities of daily living (ADL) in patients with systemic lupus erythematosus (SLE) vs healthy controls, and any associations with demographic and disease–related characteristics. Methods Hand function (grip strength, pinch strength, dexterity) and ADL performance were evaluated in 240 patients with SLE and 122 age- and gender-matched healthy controls. Grip strength, pinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…16 In the study conducted by Keramiotou et al, it was found that arthritis was reported by 18% of the participants, while joint pain was indicated by 48% of them. 13 We believe that such a high rate is related to the presence of arthritis and arthralgia in about half of the group. The grip strength of the lupus low disease activity state (LLDAS) group was higher than that of the non-LLDAS group.…”
Section: Immunology and Inflammationmentioning
confidence: 90%
“…16 In the study conducted by Keramiotou et al, it was found that arthritis was reported by 18% of the participants, while joint pain was indicated by 48% of them. 13 We believe that such a high rate is related to the presence of arthritis and arthralgia in about half of the group. The grip strength of the lupus low disease activity state (LLDAS) group was higher than that of the non-LLDAS group.…”
Section: Immunology and Inflammationmentioning
confidence: 90%
“…The Purdue Pegboard Test (PPT) is objective, inexpensive, and easy to administer with high test-retest reliability 13 . Moreover, there are a wealth of studies evaluating PPT performance in Parkinsonism and other conditions 14 17 , as well as normative data for healthy aging individuals 18 . Recently, two large studies of patients with PD found a longitudinal decline in PPT performance as disease severity increased.…”
Section: Introductionmentioning
confidence: 99%